Arthroscopic Rotator Cuff Repair with and without Acromioplasty in the Treatment of Full-Thickness Rotator Cuff Tears: Long-Term Outcomes of a Multicenter, Randomized Controlled Trial. (7th December 2022) - Woodmass, Jarret M.; Al Khatib, Loiy; McRae, Sheila; Lapner, Peter; Mascarenhas, Randy; Neogi, Devdatt; MacDonald, Peter B.
Abstract : Background: The aim of this study was to reevaluate patients from a previous randomized controlled trial at a long-term follow-up to determine the long-term efficacy of subacromial decompression in patients with full-thickness rotator cuff tears. Methods: This is a secondary study based on a previous, multicenter, randomized controlled trial with patients allocated to arthroscopic rotator cuff repair with or without acromioplasty. The original study was conducted between 2003 and 2011, and the secondary study was conducted between 2015 and 2021. Patients were invited by a blinded assessor to return to complete the Western Ontario Rotator Cuff (WORC) index and a questionnaire about reoperation and to undergo a clinical assessment. If participants were unable to return, they were asked to complete the questionnaires by mail. A chart review on all participants in the original study was conducted. Results: Eighty-six patients were randomized in the original trial, with 31 of 45 from the group without acromioplasty and 25 of 41 from the acromioplasty group returning for long-term follow-up. The mean duration (and standard deviation) of follow-up was 11.2 ± 2.4 years for the group without acromioplasty and 11.5 ± 2.6 years for the acromioplasty group. There was no significant difference in WORC scores between the groups with and without acromioplasty at the time of the long-term follow-up (p = 0.30). Seven (16%) of the 45 patients in the group without acromioplasty underwent reoperation. One (2%) of the initial 41 patients allocated to acromioplasty underwent reoperation. All patients who underwent a reoperation had a Type-2 or 3 acromion. Conclusions: Patients who underwent rotator cuff repair with or without acromioplasty experienced improvement of outcomes from their preoperative level at a long-term follow-up (mean, 11 years), and there were no differences in patient-reported outcomes, specifically WORC scores, between these groups. However, a significantly higher reoperation rate was observed in patients who had rotator cuff repair without acromioplasty, specifically in those with a Type-2 or 3 acromion. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.